A short note: Muslim Jurists’ view on surrogate motherhood - Hashi, Abdurezak Abdulahi (IIUM Press, International Islamic University Malaysia, 2019)
Surrogacy and infertility treatment are closely related, yet these two practices are different in some aspects. This is so because, infertility treatment is often sought by the infertile married couples, who wish to have children through artificial insemination, and in some cases by means of in-vitro fertilization (IVF). For infertile married couples, the fertilized egg is from the intended mother who is the legitimate wife of the intended father; without involving a third party, thus it does not involve surrogacy. In the practices of artificial insemination wherein infertility treatment involves another female, other than the intended legitimate mother (this female has the fertilized egg implanted into her womb and until birth), then in this case infertility treatment involves surrogacy; not all forms of surrogacy are sought due to infertility treatment, while not all infertility treatments are solved through surrogacy. Since the raise of infertility treatments and the practices of surrogacy, ethical and legal concerns have been raised time and again. In this short note, Muslim jurists’ view on moral concerns of surrogacy is addressed.